PENERAPAN LKPD BERBASIS STEAM PADA MATERI PERPINDAHAN KALOR DI SMA NEGERI 1 TELUK KERAMAT - Delpiaghita, Vierin; Sitompul, Stepanus Sahala; Habellia, Ray Cinthya (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
The implementation of STEAM-based student worksheets (LKPD) was triggered by seeing the conditions in the field, namely the low learning outcomes of class XI MIPA students at SMA Negeri 1 Teluk Keramat. Some of the factors that cause this problem to arise are that students are not directly involved in learning, the teacher's methods of learning are still teacher-centered, and the use of learning media is less varied. This study aims to determine student responses and the impact of using STEAM-based student worksheets (LKPD) on heat transfer material on improving student learning outcomes at SMA Negeri 1 Teluk Keramat. This research used a pre-experimental method with a one-group pretest-posttest design. The sample used was 29 students from class XI MIPA 2. The results showed that the students' response to the STEAM-based LKPD was very positive, reaching a percentage of 89.6%. In addition, there was an increase in the average score of students' learning outcomes from the pretest results, which was 57.93 to 82.76 during the posttest. The results of the N Gain test were also obtained, namely 0.54, which was included in the medium category. Based on the results of the analysis of the data obtained, it can be concluded that the application of STEAM-based worksheets on heat transfer material is effective in improving student learning outcomes.